Efektivitas Pelaksanaan Program Stunting di Kabupaten Buton Tengah: Effectiveness of Stunting Program Implementation in Buton Tengah Regency - Prasetyani, Reyni; Tenri, Andi; Asmiddin, Asmiddin (Jurnal Sains dan Kesehatan, 2024)
Stunting is a condition where a person has a height that is not in accordance with their age. The stunting condition in Buton Tengah Regency is one of the highest in Southeast Sulawesi Province. To find out the extent of the implementation of the stunting reduction program in Buton Tengah Regency, it is necessary to analyze the effectiveness of the stunting program with a decrease in the incidence of stunting in Buton Tengah Regency in 2023. This study is a non-experimental descriptive study by looking at the effectiveness of the stunting program with a decrease in the prevalence of stunting in Buton Tengah Regency in 2023. The results of the analysis show that there was an increase in the prevalence of stunting from 2022 to 2023, namely from 1621 stunting incidents to 1805 incidents. This shows that the stunting program in Buton Tengah Regency has not been effective in reducing the incidence of stunting as a whole in Buton Tengah Regency. However, the stunting program has been effective in reducing the incidence of stunting in three sub-districts, namely Gu, East Mawasangka, and Sangia Wambulu Districts. Keywords:          effectiveness, program, stunting   Abstrak Stunting adalah suatu kondisi seseorang memiliki keadaan tinggi badan yang tidak sesuai dengan umurnya. Kondisi stunting di Kabupaten Buton Tengah menduduki salah satu urutan tertinggi di Provinsi Sulawesi Tenggara. Untuk mengetahui sejauh mana implementasi program penurunan stunting di Kabupaten Buton Tengah, maka perlu dilakukan analisis efektivitas program stunting dengan penurunan angka kejadian stunting di Kabupaten Buton Tengah Tahun 2023. Penelitian ini merupakan penelitian deskriptif non eksperimental dengan melihat efektivitas program stunting dengan penurunan prevalensi stunting di Kabupaten Buton Tengah Tahun 2023. Hasil analisis menunjukkan bahwa terjadi kenaikan prevalensi stunting dari tahun 2022 ke tahun 2023, yaitu dari kejadian stunting sebesar 1621 menjadi sebesar 1805 kejadian. Hal ini menunjukkan bahwa program stunting di Kabupaten Buton Tengah belum efektif dalam menurunkan kejadian stunting secara menyeluruh di Kabupaten Buton Tengah. Namun, program stunting telah efektif menurunkan kejadian stunting di tiga kecamatan yaitu Kecamatan Gu, Mawasangka Timur, dan Sangia Wambulu. Kata Kunci:         efektivitas, program, stunting